LIBRARY SYSTEM USING QR CODE WEB WITH CODEIGNITER FRAMEWORK - Ernanda Setiawan; Arpan Arpan; Zulfahmi Syahputra (INFOKUM, 2022)
PAB 5 State Elementary School Library is an educational institution with a complete collection of library materials. A general collection of books provided for library visitors in the textbook collection. In the workflow, the process of storing and borrowing library materials is still done manually, without using an information system to improve the quality of service for librarians or administrators. These conditions became the basis for developing a library system using a web-based QR code using the CodeIgniter Framework. The Waterfall method is used to develop the system, CodeIgniter is used to create the framework, and MySQL is used to store the database. The system built at SD PAB 5 can improve the performance of library services in terms of efficiency and efficiency, and can reduce errors in processing library materials because it uses a QR code.